Estación de la Sabana reminiscencia del paisaje cultural industrial ferroviario (2021)
This degree project seeks as an approach the contemporary intervention in real estate that contains purely patrimonial characteristics in the national context, specifically The railway complex of La Estación de la Sabana located in the city of Bogotá in the department of Cundinamarca, being one of the buildings of the most important railway stations in Colombia spaces that witnessed great social interaction and that occupy a prominent place in the individual and collective memory of the communities in which they are located, thus forming an architectural unit representative of a time of the country's development.